2022
DOI: 10.1101/2022.11.04.515267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct energy-coupling factor transporter subunits enable flavin acquisition and extracytosolic trafficking for extracellular electron transfer inListeria monocytogenes

Abstract: A variety of electron transfer mechanisms link bacterial cytosolic electron pools with functionally diverse redox activities in the cell envelope and extracellular space. InListeria monocytogenes, the ApbE-like enzyme FmnB catalyzes extracytosolic protein flavinylation, covalently linking a flavin cofactor to proteins that transfer electrons to extracellular acceptors.L. monocytogenesuses an energy-coupling factor (ECF) transporter complex that contains distinct substrate-binding, transmembrane, ATPase A, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…In a previous study, Ndh3, DMK, and EetA were shown to be important for the ferric reductase activity of washed E. faecalis cells [ 14 ]. The present work demonstrates that EetB is also required, which is consistent with other studies [ 26 , 27 , 37 ]. The direct electron donor(s) to ferric ion in the cell envelope of E. faecalis and other Gram-positive electrogenic bacteria, such as Listeria monocytogemes and Lactiplantibacillus plantarum , is not known.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In a previous study, Ndh3, DMK, and EetA were shown to be important for the ferric reductase activity of washed E. faecalis cells [ 14 ]. The present work demonstrates that EetB is also required, which is consistent with other studies [ 26 , 27 , 37 ]. The direct electron donor(s) to ferric ion in the cell envelope of E. faecalis and other Gram-positive electrogenic bacteria, such as Listeria monocytogemes and Lactiplantibacillus plantarum , is not known.…”
Section: Discussionsupporting
confidence: 94%
“…However, PplA is not required for EET to Fe 3+ in E. faecalis [ 14 ] and recent experimental findings in Listeria monocytogenes show that EetB is a FAD-binding protein [ 37 ]. EetB is now suggested to be the substrate-binding component of an energy-coupled factor transporter that delivers FAD to FmnB, which is active on the outer side of the cytoplasmic membrane, catalyzing the covalent binding of FMN to a family of proteins [ 37 , 38 ]. The role of EetA is not known, but the protein seems tightly connected to the function of EetB [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…87 Recombinant reductase production and purification Hexa-histidine-tagged reductase constructs were expressed in E. coli Rosetta cells using either the pET28a or pMCSG53 expression vectors, as previously described. 88 Briefly, expression was performed using 500 mL cultures of Luria-Bertani broth (BD LB Broth, Miller #244610) + 100 µM riboflavin, grown to an OD of 0.7-1.0 at 37 °C, then induced with 1 mM β-d-1-thiogalactopyranoside overnight at 20 °C. Kanamycin (30 mg/mL, pET28a vector) or carbenicillin (100 mg/mL, pMCSG53 vector) were used for selection.…”
Section: Proteomics Mass Spectrometrymentioning
confidence: 99%